Optical asymmetric double-image encryption and authentication in an interference-based scheme using sparse representation - Luan, Guangyu; Huang, Caojun (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
We report an optical asymmetric scheme for double-image encryption and authentication based on interference using sparse representation. We employ sparse representation and interference to process the Fresnel spectra related with the two original images, and then respectively acquire two ciphertexts and two pairs of private keys. Each original image possesses its corresponding two private keys. Furthermore, the decrypted image is compared with its corresponding plaintext with the aid of a nonlinear correlation for authentication. In the proposed scheme, any information concerning each primary image and comprising its silhouette cannot be recognized even though one, two, or even three masks of the two ciphertexts and two private keys are utilized for decryption. The Fresnel spectrum functions which have different diffraction distances enhance the security of the proposal significantly. Moreover, the proposal also avoids the crosstalk problem. The effectiveness and security of this proposed method are demonstrated via numerical simulations.
Optica Applicata, Vol. 52, 2022, nr 4, s. 497-510
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; optical encryption; asymmetry; interference; double-image; authentication